2015
DOI: 10.1016/j.celrep.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The Adhesion GPCR Latrophilin/CIRL Shapes Mechanosensation

Abstract: G-protein-coupled receptors (GPCRs) are typically regarded as chemosensors that control cellular states in response to soluble extracellular cues. However, the modality of stimuli recognized through adhesion GPCR (aGPCR), the second largest class of the GPCR superfamily, is unresolved. Our study characterizes the Drosophila aGPCR Latrophilin/dCirl, a prototype member of this enigmatic receptor class. We show that dCirl shapes the perception of tactile, proprioceptive, and auditory stimuli through chordotonal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
182
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 163 publications
(203 citation statements)
references
References 49 publications
17
182
3
1
Order By: Relevance
“…1B) (Scholz et al, 2015). Genetic experiments further demonstrated that Latrophilin/dCirl activity may regulate the input-output function of mechanosensory nerve cells through the modulation of transient receptor potential channels, which ultimately govern the electrical response of these neurons (Scholz et al, 2015).…”
Section: Animal Models To Discover and Validate Molecular Conceptsmentioning
confidence: 99%
“…1B) (Scholz et al, 2015). Genetic experiments further demonstrated that Latrophilin/dCirl activity may regulate the input-output function of mechanosensory nerve cells through the modulation of transient receptor potential channels, which ultimately govern the electrical response of these neurons (Scholz et al, 2015).…”
Section: Animal Models To Discover and Validate Molecular Conceptsmentioning
confidence: 99%
“…For GPR126 in peripheral nervous system development, Stachel exposure may require interaction with the ECM molecule Laminin-211, which directs subsequent mechanical activation as proposed by Petersen et al (2015). Mechanical stimulation of aGPCR has also been suggested for Latrophilin/CIRL in sensory neurons (Scholz et al, 2015), while other studies have shown a direct activation of aGPCRs through interactions with collagens (Luo et al, 2014;Paavola et al, 2014).…”
Section: In Vitro Pharmacology Of Agpcrsmentioning
confidence: 98%
“…Complementary evidence for mechanical activation of aGPCR signals in vivo comes from recent studies on the ADGRL homolog Latrophilin/CIRL of the vinegar fly D. melanogaster (Scholz et al, 2015). Here, the aGPCR is resident in mechanosensory neurons, which-upon mechanical stimulation through sound, touch, or stretch-respond adequately with an increase in electrical activity.…”
Section: In Vivo Mechanisms Of Agpcr Activationmentioning
confidence: 99%
“…An emerging concept is that ECM proteins mechanically modulate signaling properties of adhesion GPCRs [11,22,25], and in the future it will be interesting to understand how different ECM signals converge to control Gpr126/Adgrg6 signaling. In humans, mutations in LAMA2, encoding the α2 chain of Laminin-211, cause merosin-deficient congenital muscular dystrophy (MDC1A) with dysmyelination [26][27][28], suggesting that modulation of GPR126/ADGRG6 might be efficacious in these patients.…”
Section: Schwann Cell Developmentmentioning
confidence: 99%